Exploring the potential of TikTok as a learning resource for enhancing scientific writing skills in physical education - Vai, Aref; Desviyanti, Elsya; Ndayisenga, Japhet; Ahmadi, Dedi; Nevitaningrum (Edu Sportivo: Indonesian Journal of Physical Education, 2023)
Technological advancements have permeated the field of education, including the use of multimedia-based learning materials in the learning process. This study aims to help students of the Department of Physical Education at Universitas Riau overcome the obstacles they face when writing scientific papers, especially when preparing a thesis. By harnessing the potential of TikTok social media as a learning resource, it is anticipated that students’ interest and motivation, especially in scientific writing, will be enhanced. This research adopts a quantitative descriptive approach and employs the survey method, utilisingutilizing a questionnaire as the research instrument and descriptive statistics as the data analysis technique. The population and sample of this study consisted of 26 students from the 2020 class of the Department of Physical Education at Universitas Riau. Findings showed that 9 students (34.6%) strongly agreed, 10 students (38.5%) agreed, and 7 students (26.9%) expressed neutrality towards utilizing TikTok social media as a learning medium. The results suggest that TikTok social media can serve as a catalyst for students’ curiosity, facilitating the learning of scientific writing, and fostering increased enthusiasm and interest in the learning process. Future research should consider expanding the sample size and incorporating comparison groups to gain further insights in this field. This study contributes by providing initial evidence on the potential of TikTok as a learning resource, highlighting its impact on students’ motivation and interest in scientific writing, and identifying opportunities for integrating social media in higher education to overcome writing obstacles.